2011
DOI: 10.1007/s13361-011-0286-6
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Demonstration of an IonCCD as an Alternative Pixelated Anode for Direct MCP Readout in a Compact MS-Based Detector

Abstract: We report on the preliminary testing of a new position-sensitive detector (PSD) by combining a microchannel plate (MCP) and a charge-sensitive pixilated anode with a direct readout based on charge-coupled detector (CCD) technology, which will be referred to as IonCCD (Hadjar et al. , allowing it to be used directly behind an MC. This MCP-IonCCD configuration potentially obviates the need for electro-optical ion detector systems (EOIDs), which typically feature a relatively difficult-to-implement 5-kV power sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
1
8
0
5
Order By: Relevance
“…These could be used in applications where both single-photon sensitivity and high temporal resolution are required, like simultaneous positron emission tomography and magnetic resonance imaging3334, today's hot topic in medical diagnostic. Finally, an AMCP vertically integrated on charge-coupled arrays (CCDs) could provide a variant of electron-bombarded CCD3536 (ebCCD) to be used in single-molecule spectroscopy1037 or mass spectrometry9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These could be used in applications where both single-photon sensitivity and high temporal resolution are required, like simultaneous positron emission tomography and magnetic resonance imaging3334, today's hot topic in medical diagnostic. Finally, an AMCP vertically integrated on charge-coupled arrays (CCDs) could provide a variant of electron-bombarded CCD3536 (ebCCD) to be used in single-molecule spectroscopy1037 or mass spectrometry9.…”
Section: Discussionmentioning
confidence: 99%
“…Microchannel plates1 (MCPs) are well-established electron multipliers that were initially developed for night vision applications and astrophysics23 and progressively spread into different fields such as nuclear45 and plasma67 physics, mass spectrometry89 and biotechnology10. Electron multiplication in MCPs takes place inside long thin channels (also called pores), which replace the cascade of discrete dynodes in traditional photomultipliers.…”
mentioning
confidence: 99%
“…One possibility to increase the sensitivity (and improve the detection limits for ICP-DOFMS) of the IonCCD camera is to add a preamplification stage to the detector. In a previous study, the IonCCD camera was shown to function as an effective anode for direct-MCP readout [28]. By the addition of an MCP as a pre-amplification stage, the IonCCD camera would gain three to four orders of magnitude in sensitivity.…”
Section: Lumentioning
confidence: 99%
“…This source, along with a narrower object slit, may also be considered for use in conjunction with the MCP-enhanced IonCCD in an MH-MS. 25,29 Here the increased resolving power attributed to the narrower slit would be expected to more than offset the loss in resolving power caused by the MCP, and most of the large anticipated sensitivity increase for this system would arise from the inherently high gain of the MCP.…”
Section: Summary and Applicationsmentioning
confidence: 99%
“…24) used in the work reported here, offer virtually no inherent signal gain, which places them at an inherent disadvantage relative to secondary electron-multiplier type detectors, even though much of the resulting sensitivity deficit can be offset by the simultaneous and continuous nature of non-scanning MH-MS detection. In another previous study, 25 therefore, we demonstrated the potential for addressing this sensitivity issue by using the IonCCD as an anode to directly readout a microchannel plate (MCP), by analogy to an earlier work using a different chip design. 26,27 The MCP increased the signal-tonoise ratio by a factor of about 3000 while keeping the instrument size unchanged, although mass spectral peaks were somewhat broadened, causing a loss of resolving power.…”
Section: Introductionmentioning
confidence: 98%